Gps Enabled Vehicle Location Identification Using Gsm And Fare Collection Using Smart Card - et. al., k.G.Revathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This project explains that the prediction of bus arrival time and bus location information to the passengers in their respective bus stops through GSM and GPS and by measuring the speed by accelerometer. It includes that the unmanned vehicle(i.e. bus) driver and passengers journing without conductor. It also include an automated fare collection system through passengers onboard smart card tickets. Our project provides vehicle location updated information to the passengers and other additional information's are, number of passengers onboard while starting the bus in the starting point and how many of them off board and onboard in point to point stopping information and also provides final passengers information through GSM to ticket checker and other higher officials and also an information viewed by driver through electronic LCD board.